A nanocomplex that is both tumor cell-selective and cancer gene-specific for anaplastic large cell lymphoma - Zhao, Nianxi (BioMed Central, 2011)
BACKGROUND: Many in vitro studies have demonstrated that silencing of cancerous genes by siRNAs is a potential therapeutic approach for blocking tumor growth. However, siRNAs are not cell type-selective, cannot specifically target tumor cells, and therefore have limited in vivo application for siRNA-mediated gene therapy. RESULTS: In this study, we tested a functional RNA nanocomplex which exclusively targets and affects human anaplastic large cell lymphoma (ALCL) by taking advantage of the abnormal expression of CD30, a unique surface biomarker, and the anaplastic lymphoma kinase (ALK) gene in lymphoma cells. The nanocomplexes were formulated by incorporating both ALK siRNA and a RNA-based CD30 aptamer probe onto nano-sized polyethyleneimine-citrate carriers. To minimize potential cytotoxicity, the individual components of the nanocomplexes were used at sub-cytotoxic concentrations. Dynamic light scattering showed that formed nanocomplexes were ~140 nm in diameter and remained stable for more than 24 hours in culture medium. Cell binding assays revealed that CD30 aptamer probes selectively targeted nanocomplexes to ALCL cells, and confocal fluorescence microscopy confirmed intracellular delivery of the nanocomplex. Cell transfection analysis showed that nanocomplexes silenced genes in an ALCL cell type-selective fashion. Moreover, exposure of ALCL cells to nanocomplexes carrying both ALK siRNAs and CD30 RNA aptamers specifically silenced ALK gene expression, leading to growth arrest and apoptosis. CONCLUSIONS: Taken together, our findings indicate that this functional RNA nanocomplex is both tumor cell type-selective and cancer gene-specific for ALCL cells.